Efficacy and Safety of New Lactobacilli Probiotics for Unconstipated Irritable Bowel Syndrome: A Randomized, Double-Blind, Placebo-Controlled Trial - Oh, Joo Hyun (Nutrients, 2019)
Irritable bowel syndrome (IBS) is a common and chronic gastrointestinal disorder. Probiotics may have the potential to impact the management of IBS; however, the results of trials are conflicting. This study aimed to investigate whether a mixture of lactobacilli probiotics could improve abdominal symptoms in patients with unconstipated IBS. Fifty Vietnamese patients with unconstipated IBS were randomly assigned to either the probiotics or placebo groups. During the intervention, participants took the probiotic supplement, named Foodis Lactobacillus, or placebo capsule once a day. Patients recorded their subject global assessment (SGA) weekly and were assessed with the visual analogue scale (VAS) during the 4-week study period. Patients with SGA score of 2 points or more or a decrease of more than 30% in VAS score were considered responders. Patients who responded weekly for more than 2 of the 4 weeks were considered overall responders. There was no significant difference in demographic characteristics between the groups. Overall responder rates of improvement of global IBS symptoms assessed by SGA score were significantly higher in the probiotics group (80.8%) than in the placebo group (45.8%) (p = 0.009). The overall responder rates assessed by VAS score were also higher in the probiotics group (69.2%, 41.7%, p = 0.048). There were no adverse events in either group during the study period. Our findings suggest that the new combination of Lactobacilli appears to be promising in the relief of abdominal symptoms in Vietnamese patients with unconstipated IBS.